Children’s views on weight measurement and talking about weight - Ryan Herbert; Fiona Gillison; Elisabeth Grey; Abigail Hewitt; Alice Woods; Charlotte Jackson; Grace Wisbey; Jack Perks; Maddy Longhurst (BMC Public Health)
Abstract Background Parents are considered important in promoting children’s healthy weight, but express concern about how to talk to children about weight without harming their wellbeing. However, there is little research with children themselves as to what they expect and want in relation to managing their weight. This study aimed to explore children’s views about weight measurement, and whether and how information about their weight should be shared with them. Methods Primary school-aged children were recruited through their school to take part in focus groups. Discussions were focused around two tasks: drawing a shared mind map of sources of information about weight; and exploring responses to a structured story about a child’s experience of being weighed and measured. The discussions were recorded, transcribed and analysed using thematic analysis. Results Forty-eight children took part, across eight focus groups. Theme 1 explored how children considered that most weight discussions were peripheral to them, often overheard conversations related to family members’ attempts at weight loss. Theme 2 showed how children empathised with the challenges parents face when deciding whether to disclose weight status, in balancing the desire to avoid upsetting children with the desire to be honest and action focussed. Theme 3 summarised children’s expectations about what should happen if children are found to have overweight or obesity, emphasising a whole-family approach. Conclusion Children’s views about how and whether to talk about weight varied, but appeared underpinned by the awareness of stigma and belief in individual responsibility and capability for controlling body weight.